1990
DOI: 10.1002/app.1990.070411133
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity of aqueous solutions of polysaccharides and their carboxylate derivatives

Abstract: SynopsisThe viscosities of aqueous solutions of methyl cellulose, dextran, and their carboxymethyl derivatives were measured as functions of molecular weight and concentration. Furthermore, effects of ionic group and added salt on the viscosity of aqueous solutions of carboxymethyl derivatives were investigated. The viscosities of dextran and carboxymethyl dextran solutions did not show any shear stress dependence, but those of methyl and carboxymethyl cellulose solutions strongly depended on shear stress even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
2
4
1
Order By: Relevance
“…The hydrodynamic properties of aqueous dextran solutions were investigated. At a high concentration of 30 wt %, D50, whose M w was 5.223 × 10 5 , behaved as a pseudoplastic fluid, and this conflicted with the findings by other scientists,10–12 whereas the rest of the experimental results from rheological tests with a low M w value or a low concentration agreed very well with others' results; that is, the aqueous solutions expressed Newtonian properties. In thixotropic property tests, most dextran solutions did not form a thixotropic loop, except for the 30 wt % solution of D50.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The hydrodynamic properties of aqueous dextran solutions were investigated. At a high concentration of 30 wt %, D50, whose M w was 5.223 × 10 5 , behaved as a pseudoplastic fluid, and this conflicted with the findings by other scientists,10–12 whereas the rest of the experimental results from rheological tests with a low M w value or a low concentration agreed very well with others' results; that is, the aqueous solutions expressed Newtonian properties. In thixotropic property tests, most dextran solutions did not form a thixotropic loop, except for the 30 wt % solution of D50.…”
Section: Discussioncontrasting
confidence: 63%
“…Carrasco et al10 found that all solutions of dextrans with molecular weights ranging from 71,500 to 531,000 and with concentrations up to 30 wt % behaved as Newtonian fluids. Nomura et al11 also found that the solution viscosity of dextrans with molecular weights ranging from 10 4 to 2 × 10 6 and concentrations ranging from 0.5 to 30 wt % to be independent of the shear stress. Tirtaatmaja et al12 also confirmed this point of view by employing dextrans with M w values ranging from 40,000 to 2,000,000 and with concentrations up to 30 wt %.…”
Section: Introductionmentioning
confidence: 96%
“…It is known that the molecular weight would increase due to the number of -OCH 2 COONa groups per glucose unit that also increase the hydrodynamic volume of CMSC. This was shown in another study done by Nomura et al [62] regarding about viscosity of CMC and carboxymethylation of dextran [63]. In Table 4, the solubility of CMSC is high (95% dissolved) is attributable to the carboxylate group appended to the cellulose backbone [64].…”
Section: Moisture Contentmentioning
confidence: 52%
“…Further evidence of the role played by chain flexibility on the non-Newtonian properties of dilute solutions comes from dextran, the archetype of 'true' random coil polysaccharides. For dextran systems, in fact, the lower Newtonian plateau extends to elevated y values, even for high molecular weight samples [24,25].…”
Section: J Steady Shear Viscositymentioning
confidence: 95%